Peroral endoscopic pyloromyotomy accelerates gastric emptying in healthy pigs: proof of concept - Geyl, Sophie; Legros, Romain; Charissou, Aurélie; Mesturoux, Laura; Couquet, Claude-Yves; Carrier, Paul; Brayette, Anaïs; El-Ouafi, Zora; Loustaud-Ratti, Veronique; Sautereau, Denis; Monteil, Jacques; Jacques, Jérémie (Endoscopy International Open, 2016)
Introduction: Gastroparesis, or delayed gastric emptying, can be diagnosed with gastric emptying scintigraphy. Manometric studies of patients with gastroparesis show increased pyloric tone (pylorospasm). Among the recent endoscopic therapies for pylorospasm is peroral endoscopic pylorotomy (POP). In this study, we explored the effect of POP on gastric emptying in healthy pigs.Material and methods: Four mini-pigs underwent POP following general anaesthesia. The mucosal entrance was situated 5 cm above the pylorus. POP was performed through a submucosal tunnel dissection. The duration of gastric emptying was assessed by scintigraphy before and after the procedure. The pigs were then euthanised for necropsy and pathologic assessment of the pylorus.Results: The mean duration of the procedure was 55 (± 4 SD) min. All surgeries were performed in their entirety with 100 % feasibility. There were no cases of bleeding. The one case of perforation had no clinical significance. The duration of gastric emptying was 2.22-fold shorter after POP compared with before POP (T½ post-POP = 84.5 [± 35.7 SD] min vs. T½ pre-POP = 188.4 [± 87.3 SD] min; P = 0.029). In agreement with the endoscopic observations, sectioning of the pyloric muscle in each pig was histologically complete.Conclusion: The efficacy of the procedure provides indirect proof of the involvement of the pyloric ring in delayed gastric emptying and suggests new therapies for patients with gastroparesis. Our protocol combining gastric emptying scintigraphy and POP validated the use of anaesthetised mini-pigs as a learning and training model for POP or other endoscopic/surgical procedures related to gastric emptying.